Discrete‐time dynamic event‐triggered H∞ control of uncertain neural networks subject to time delays and disturbances - Huong, Dinh Cong (Optimal control applications & methods, 2023)
The event‐triggered H∞$$ H_{∞ } $$ control problem for uncertain neural networks subject to time‐varying delays and disturbances was considered in this article. A method based on a novel discrete‐time dynamic event‐triggered mechanism and an event‐triggered control is proposed to solve the problem of event‐triggered H∞$$ H_{∞ } $$ control for the considered neural networks. By employing the Lyapunov–Krasovskii functional method, the Cauchy matrix inequality, and the Schur complement lemma, we derive a sufficient condition to guarantee the event‐triggered H∞$$ H_{∞ } $$ control problem is solved. This sufficient condition is formed in terms of linear matrix inequalities, which can be effectively solved by using the MATLAB LMI Control Toolbox. Two examples and simulations are provided to illustrate the efficiency of the proposed method.